Perioperative SBP changes during orthopedic surgery in the elderly: clinical implications. Issue 8 (August 2019) - Koutsaki, Maria; Thomopoulos, Costas; Achimastos, Apostolos; Kallistratos, Manolis; Batistaki, Chrisanthi; Chatziagelaki, Erifili; Soulioti, Eleftheria; Poulimenos, Leonidas; Koutsaki, Stella; Mela, Argiro; Mancia, Giuseppe; Manolis, Athanasios J.
Abstract : Objectives: We aimed to determine SBP changes during the perioperative period of a scheduled knee surgery under regional anesthesia and the extent of perioperative (in-hospital) white-coat effect. Methods: All patients (aged ≥60 years) underwent clinic SBP measurements during both cardiological and anesthesiological visits, while home SBP the week before admission was obtained. Clinic SBP was registered just before surgery, during surgery and reanimation. Ambulatory monitoring was also performed (12 h before surgery to 6–8 h after surgery). One month after discharge, clinic SBP was measured at hypertension unit. Results: Eligible participants ( N  = 50, mean age 74 ± 7 years, 34% men, 26% with history of cardiovascular disease) had higher SBP during the anesthesiologic than the cardiological evaluation (157 ± 23 vs. 144 ± 18 mmHg, P  < 0.001), and the former levels were almost identical to those clinically measured just before surgery. A significant white-coat effect between ambulatory and clinic measurements just before surgery (16.4 ± 21 mmHg, P  < 0.001) and between entire ambulatory recording and clinic BP measurements the day before surgery (12.4 ± 16 and 24.8 ± 21 mmHg for cardiologic and anesthesiologic visit, respectively, P  < 0.001 for both) was noticed, whereas intraoperatively the white-coat effect faded away. There was a greater SBP decline during surgery in patients aged more than 75 years compared with younger, whereas selective treatment discontinuation (except beta blockers and calcium channel blockers) did not modulate SBP trajectories. Conclusion: The significant white-coat effect observed in scheduled noncardiac surgery is clinically important and the home BP measurement performed before surgery or ABPM, highly reflects the hypertensive burden of the patient. Blood pressure decrease during surgery is quite pronounced especially in patients aged more than 75 years. Aggressive BP lowering should be avoided. Abstract : Supplemental Digital Content is available in the text